Affective societies : key concepts. - Slaby, Jan.; Scheve, Christian von. (Abingdon, Oxon : Routledge, 2019)
Affect and emotion have come to dominate discourse on social and political life in the mobile and networked societies of the early 21st century. This volume introduces a unique collection of essential concepts for theorizing and empirically investigating societies as Affective Societies. The concepts promote insights into the affective foundations of social coexistence and are indispensable to comprehend the many areas of conflict linked to emotion such as migration, political populism, or local and global inequalities. Adhering to an instructive narrative, Affective Societies provides historical orientation; detailed explication of the concept in question, clear-cut research examples, and an outlook at the end of each chapter. Presenting interdisciplinary research from scholars within the Collaborative Research Center "Affective Societies," this insightful monograph will appeal to students and researchers interested in fields such as affect and emotion, anthropology, cultural studies, and media studies.
Part II: Elaborating affectChapter 9: Affective arrangement; Arrangement thinking: key dimensions; Background and related concepts; Examples from research; Conclusion: two methodological orientations; References; Chapter 10: Affective disposition; Example; Related concepts across disciplines; Psychology; Sociology; The authoritarian personality; Systematic elaboration; Outlook and applications; References; Chapter 11: Affective practice; An outline of praxeology; The affective dimension of practice; Affective phenomena in practice; The accountability of affect; References
OCLC-licensed vendor bibliographic record.
Keywords: Affect (Psychology) -- Social aspects; Emotions -- Sociological aspects; PSYCHOLOGY / Physiological Psychology; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General